Perspectives of COVID‐19 vaccine–hesitant emergency department patients to inform messaging platforms to promote vaccine uptake. (22nd November 2022) - Gentsch, Alexzandra T.; Butler, Jonathan; O'Laughlin, Kelli; Eucker, Stephanie A.; Chang, AnnaMarie; Duber, Herbie; Geyer, Rachel E.; Guth, Amanda; Kanzaria, Hemal K.; Pauley, Alena; Rising, Kristin L.; Chavez, Cecilia Lara; et al.
Abstract: Objectives: Efforts to promote COVID‐19 vaccine acceptance must consider the critical role of the emergency department (ED) in providing health care to underserved patients. Focusing on patients who lacked primary care, we sought to elicit the perspectives of unvaccinated ED patients regarding COVID‐19 vaccination concerns and potential approaches that might increase their vaccine acceptance. Methods: We conducted this qualitative interview study from August to November 2021 at four urban EDs in San Francisco, California; Seattle, Washington; Durham, North Carolina; and Philadelphia, Pennsylvania. We included ED patients who were ≥18 years old, fluent in English or Spanish, had not received a COVID‐19 vaccine, and did not have primary care physicians or clinics. We excluded patients who were unable to complete an interview, in police custody, under suspicion of active COVID‐19 illness, or presented with a psychiatric chief complaint. We enrolled until we reached thematic saturation in relevant domains. We analyzed interview transcripts with a content analysis approach focused on identifying concerns about COVID‐19 vaccines and ideas regarding the promotion of vaccine acceptance and potential trusted messengers. Results: Of 65 patients enrolled, 28 (43%) identified as female, their median age was 36 years (interquartile range 29–49), and 12 (18%) interviews were conducted in Spanish. Primary concerns about COVID‐19 vaccines included risk of complications, known and unknown side effects, and fear of contracting COVID‐19 from vaccines. Trust played a major role for patients in deciding which sources to use for vaccine information and in engendering vaccine acceptance. Health care providers and family or friends were commonly cited as trusted messengers of information. Conclusions: We characterized concerns about COVID‐19 vaccines, uncovered themes that may promote vaccine acceptance, and identified trusted messengers—primarily health care professionals. These data may inform the development of nuanced COVID‐19 vaccine messaging platforms to address COVID‐19 vaccine hesitancy among underserved ED populations.